Process plants : a handbook for inherently safer design - Kletz, Trevor A.; Amyotte, Paul. (Boca Raton, FL : CRC Press, 2010)
This resource covers the design of inherently safer and user-friendly plants. It demonstrates how chemical plants can withstand human error and equipment failures without serious effects on safety, output, or efficiency.
Includes bibliographical references and index.
Keywords: Chemical plants -- Safety measures